Central Bank Digital Currencies and payments: A review of domestic and international implications - Demmou, Lilas (OECD Economics Department Working Papers, 2021)
Recent technological developments linked to secure messaging and traceability present an opportunity to address certain challenges in international and domestic payment systems. From an international perspective, foreign exchange markets remain costly and relatively less efficient than domestic payment systems. From a domestic perspective, the decline in the relative importance of cash in most economies reflects changes in consumers' preferences, which questions the future of money and payment infrastructure. Against that background, private initiatives falling outside of current regulation, such as stable coins and other virtual assets, are associated with several risks and opportunities and have fueled the debate on the opportunities for central banks to issue new form of digital public currency. This note reviews those different propositions and examine their implication for the international and domestic payment systems